Law, Freedom, and Slavery. Issue 1 (15th February 2022) - Neoh, Joshua
Abstract: This paper argues that the wrong of slavery lies in the denial of the good of law to the slave. Defending this proposition will require the positing of three related claims: (i) that law is good, (ii) that the good of law is denied to the slave, and (iii) that the denial is wrong. This paper will defend the main proposition by defending its three constituent claims. On claim (i), the paper will relate the form of law to the formation of freedom. On claim (ii), the paper will relate law's objectivity to legal subjectivity. On claim (iii), the paper will relate the state of nature to the state of civil society.